Emerging market hedge funds: are they managed like hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2013)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period showthat EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: dept.fin; ⛔ No DOI found

Are we overestimating REIT idiosyncratic risk? Analysis of pricing effects and persistence - Abugri, Benjamin A.; Dutta, Sandip (International Review of Economics & Finance, 2014)
This study uses a multifactor REIT-specific model to estimate and compare REIT idiosyncratic volatility vis-A-vis the same from the Fama-French three-factor model. Estimates of conditional idiosyncratic volatility and conditional betas obtained from a multifactor REIT-returns model and a bivariate EGARCH model respectively are found to be positively and significantly related with REIT returns. Consistent with Merton's (1987) predictions, we observe that larger REITs post higher average returns when idiosyncratic risk is introduced in cross-sectional regressions. Persistence of past market-risk does not appear to be short-lived and seems to have a lasting impact on future idiosyncratic volatility. We also observe mild evidence of persistence of past idiosyncratic risk, albeit short-lived, thereby suggesting that past idiosyncratic risk has a short-term impact on future idiosyncratic risk. Published by Elsevier Inc.
Keywords: Conditional betas; Idiosyncratic risk; REITs; dept.fin

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Testing trade-off and pecking order models of capital structure: does legal system matter? - Cotei, Carmen; Farhat, Joseph B; Abugri, Benjamin A (Managerial Finance, 2011)
Purpose – This paper aims to examine the link between financing patterns, information asymmetry and legal traditions in 37 countries during the 1990-2004 period. Design/methodology/approach – The analysis is based on three theories: the trade-off theory, pecking order hypothesis and market timing hypothesis. The authors test the predictions of these theories/hypotheses using regression analysis. The econometric method used is panel data with firm and country fixed effects. The authors develop a modified pecking order model which controls for short- and long-term debt level changes and simultaneously test the predictions of all theories. Findings – Consistent with studies for US firms, the results show that firms across all countries adjust toward the target leverage, but with significantly different rate. The long-term debt contribution in the rate of adjustment is 64 percent in common law countries and 51 percent in civil law countries. The ability of the model to explain changes in leverage ratios is higher in common law countries. The authors find support for market timing hypothesis but no support for pecking order of financing. These results support their conjecture that stronger investor protection, higher transparency and well-developed financial markets in common law countries reduce the cost of recapitalization. Research limitations/implications – The limitation of this study comes from lack of data availability to measure contract enforcement, transparency, and corporate governance variables. Future research can incorporate these variables to explain the differences in capital structure decisions across countries with different legal systems. Practical implications – The findings show that firms' capital structure decisions are not only a function of their own characteristics but also the result of legal and financial market development in which they operate. Originality/value – This is the first study that sheds light about rate of adjustment to optimal capital structure and pecking order of financing in 37 countries with different legal traditions and financial market developments. The authors are not aware of any other study that uses a modified pecking order model in an international context. © 2011, © Emerald Group Publishing Limited.
Keywords: Capital; Financial development; International capital structure; Legal systems; Pecking order theory; Trade-off theory; dept.fin; peer-reviewed